Hot mahogany - Woods, Stuart (New York : G.P. Putnam's Sons, 2008)
Stone Barrington gets the job of watching an army intelligence officer whose memory is muddled after an act of violence.
Keywords: Barrington, Stone (Fictitious character) -- Fiction; Private investigators -- Fiction; Mystery fiction